Vivax Malaria Presenting with Fever and Tender Hepatomegaly (Faridpur Medical College Journal, 2017)
Malaria caused by vivax is more common than those caused by falciparum. We report here a patient of vivax malaria presented with tender hepatomegaly. A 30 year old male from a rural area was admitted with high grade irregular fever for 5 days with severe right hypochondriac pain for 2 days. Patient was toxic and agonizing with pain. He had tender hepatomegaly. His cardiovascular and respiratory examination findings were normal. ICT for malaria and blood film revealed presence of P. vivax. His hepatic enzymes and viral markers were negative and ultrasonogram of hepatobiliary system excluded features of hepatitis or any abscess cavity. Echocardiogram showed no cardiac abnormality. Presence of tender hepatomegaly in the absence of other co-morbidity is rare in vivax malaria and not well documented in adults, which makes this presentation.Faridpur Med. Coll. J. Jul 2016;11(2): 90-92